Modifying the Gut Microbiome Through Diet or Antibiotics Alters Bone Phenotypes in Older Mice. (7th June 2021) - Smith, Kelsey; Castaneda, Macy; Tsai, Chia-Fang; Francisco, Sarah; Nixon, Jacob; Smith, Donald; Barger, Kathryn; Hernandez, Christopher; Rowan, Sheldon
Abstract: Objectives: Gut microbiota have been shown to influence bone quality and quantity, both risk determinants for osteoporosis. Previous research in young mice showed oral antibiotic treatment during rapid bone gain impaired bone tissue quality. We sought to determine if modifying the gut microbiome of aged mice through diet or antibiotic treatment affects bone geometry and/or strength. Methods: A high (HG) or low glycemic (LG) diet was fed in equal amounts to 12-mo. male mice. The diets differed only by starch composition, which was 100% rapidly digested amylopectin in the HG diet or 30% amylopectin/70% amylose in the LG diet. A third group received the LG diet containing antibiotics (ampicillin and neomycin; LGAbx). Feces were collected at baseline and after 10 months of treatment and 16s rRNA sequencing was performed followed by ecological diversity and differential abundance analysis. Femora were harvested after 12 months of treatment for analysis of bone geometry and strength via mechanical testing and imaging. Results: Antibiotic treatment reduced alpha diversity, including an average 92% reduction in observed OTUs from baseline compared with 30% reduction in the other groups. Both diet and antibiotic treatment significantly altered taxonomic composition, including an expansion of Proteobacteria in response to antibiotics. Whole bone strength is determined by a combination of the section modulus (the measure of geometry most closely related to bending strength) and the mechanical properties of the bone tissue itself. In HG-fed mice the section modulus was greater than that of the other groups and the bone showed a correspondingly greater strength. However, in LGAbx-fed mice the whole bone strength was 22% lower than bones with similar section modulus in the LG and HG-fed groups, indicating impaired bone tissue material properties. Conclusions: Altering diet resulted in significant changes to bone geometry and strength, while changes in the gut microbiota associated with antibiotic treatment resulted in a reduction to bone strength which could not be explained by bone geometry. Our study indicates that dietary or antibiotics treatments applied to mice later in life can alter bone properties, which suggests that interventions to improve bone strength may be effective in older adults. Funding Sources: NIH/NIAMS, BrightFocus Foundation, Stanley N. Gershoff Scholarship.